Влияние поверхности на тензор модулей упругости - Глинчук, М.Д.; Скороход, В.В.; Елисеев, Е.А.; Хист, В.В.; Зауличный, В.Я. (Доповіді НАН України, 2011)
Розглянуто зміни незалежних компонент тензорів модулів пружності поблизу плоских поверхонь для всіх 32 кристалографічних об'ємних класів. Розрахунок проведено для тензорів четвертого рангу модулів пружності та податливості на основі теорії симетрії, що враховує вплив елементів симетрії групи на компоненти тензорів. Встановлено збільшення числа ненульових компонент завдяки зниженню симетрії поблизу поверхні. Зокрема, до існуючих в об'ємі трьох незалежних пружних модулів (c11, c12, c44) слід додати c33, c13 та c66 для поверхні типу (100) та нові ненульові компоненти c14, c22=−c14, c56=−c14 для поверхні типу (111). Порівняльний аналіз величин тензорів пружності в об'ємі та поблизу поверхні показав, що співвідношення Коші не виконуються у наноструктурних матеріалах через втрату просторової інверсії атомів поблизу поверхні. На основі проведених раніше експериментальних досліджень та першопринципних розрахунків встановлено, що вплив поверхні є значним для розмірів, що не перевищують 100 нм. The consideration of a change of independent components of the tensors of elasticity moduli in a vicinity of flat surfaces for all 32 bulk crystallographic classes is carried out. The calculations are performed for the fourth rank tensors of elasticity moduli and compliances on the basis of the symmetry theory with respect to the transformation of tensor components under a symmetry group. The increase in the number of nonzero components is obtained due to the symmetry lowering in a vicinity of the surface. In particular, for the cubic symmetry, the moduli c33, c13, and c66 appear in addition to the known three nontrivial moduli (c11, c12, c44) for surfaces of the (100) type and new nonzero components c14, c22=−c14, c56=−c14 are obtained for those of the (111) type. Comparative analysis of elastic moduli in bulk and in a vicinity of the surface has shown that the Cauchy relations are not valid in a vicinity of the surface because of the inversion symmetry absence. Analysis of the experimental results and those f ab initio calculations for nanostructured materials allows us to conclude that the surface influence is essential for sizes up to 100 nm.